Modern options and prospects of treatment of resistant forms of gastroesophageal reflux disease - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss the factors promoting resistance of gastroesophageal reflux disease (GERD) to treatment and possible ways to overcome this phenomenon.Original positions. It was demonstrated, that the causes of resistant forms of GERD are diverse and connected related both to subjective factors (poor patient compliance) and to objective factors («night acid breakthrough», episodes of non-acid reflux, etc.). Potentials of treatment of resistant forms of GERD include increase of proton pump inhibitors (PPI) dose, application of parenteral forms of PPI if necessary and combination to Н2-blockers. Further prospects of improvement of acidsuppressive agents action are related to development of new generations of PPIs.Conclusion. Resistant forms of GERD are quite frequent in clinical practice. Now there are various options to increase treatment efficacy.